The Phenomenon of COVID-19 Conspiracy Theory Narratives through Virtual Ethnography on Instagram - Qorib, Fathul; Ramadan, Rangga Tirta (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
This study aims to investigate the conspiracy phenomenon of the COVID-19 pandemic as disseminated by the Instagram account @unexplnd. This account boasts 842 thousand followers and stands as one of the largest social media propagating the concept of COVID-19 conspiracy theories in Indonesia. Primary data is derived from posts on this account, and secondary data is obtained through interviews with four followers who actively engage in commenting and harbor beliefs in the existence of conspiracies. The research corpus is subsequently scrutinized employing the conceptual framework delineated by Douglas, Sutton, and Cichocka (2017), which delineates the emergence of conspiracies through epistemic, existential, and social motives. The findings of this investigation reveal that incidents perceived as random chance occurrences, motivated by the desire to preserve comfort and freedom, along with suspicion or resentment towards particular entities, serve as grounds for endorsing COVID-19 pandemic conspiracy theories. Furthermore, exposure to media presenting conspiracy theories, such as the Instagram account @unexplnd, contributes to an augmented belief in such theories among proponents. Conspiracy theorists desire to raise awareness among the general populace regarding conspiracy theories by disseminating information containing conspiracy narratives across various media channels.